The Common Aspects of Imam Sohaili and Ibn Qayyim’s Methodologies in Deriving Fiqh Rulings - Dr. Fareed Ud Din Tariq (Al-Qanṭara, 2024)
On the holy biography of the Holy Prophet (peace and blessings of Allah be upon him), while the biography of Ibn Hisham of Allama Ibn Hisham is an authentic and reliable source, his famous book "Al-Rawd al-Anaf" is also an example of his biography. Imam Suhaili's "Al-Rawd al-Anaf" contains other features, the style of "Fiqh al-Sirah" is also its distinguishing feature and it is the first book to introduce this style.Similarly, after "Al-Rawz al-Anaf" Hafiz Ibn Qayyim's "Zad al-Ma'ad" also has the uniqueness of adopting the style of "Fiqh al-Sirah" in a regular and extensive manner. Below is the description of the common aspect of the style of these two books which the authors have adopted in deriving the rulings from the events and history:The noble biography of the Holy Prophet Muhammad (peace and blessings be upon him) is not only profoundly rooted in the ''Seerat Ibn Hisham'' by Allama Ibn Hisham, a highly authentic and reliable source, but its renowned commentary, ''Al-Rawd Al-Unuf'', also stands as an unparalleled reference for Seerah studies. Imam Suhaili’s ''Al-Rawd Al-Unuf'', alongside encompassing various unique features, distinguishes itself with the introduction of the methodology of "Fiqh al-Seerah." It is the first book to pioneer this approach.Similarly, after Al-Rawd Al-Unuf, Hafiz Ibn Qayyim's Zad Al-Ma’ad also gains uniqueness in systematically and comprehensively adopting the "Fiqh al-Seerah" approach. Below is a discussion of the common methodology both authors employed in deriving legal rulings (Ahkam) from the events of the Prophet's biography.